SOME EVOLUTIONARY ASPECTS OF THE BINARY STELLAR SYSTEMS CONTAINING NEUTRON STAR - Ulyanov, Oleg O.; Andrievsky, Sergei M.; Gopka, Vera F.; Shavrina, Angelina V. (Одеські астрономічні публікації, 2012)
The obvious lack of the binary stellar systems that contain neutron stars (NS) is observed at present. Partly it is caused by the fact that it is very difficult to detect neutron star in a binary system if this relativistic component does not manifest itself as a radio pulsar. Among 1879 pulsars that are listed in the ATNF pulsar catalogue, only 141 pulsars are known to be the companions in binary systems. Only 81 objects having median mass estimation of more than 0.2 Msun constitute the binary systems with pulsars. Nevertheless, such systems should be much more numerous and their investigation is of the great interest because thier structure and evolution can certainly help in our understanding of many unique properties that are seen in some stars.